2020
DOI: 10.1155/2020/8832739
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 5-Gene Signature Improves Lung Adenocarcinoma Prognostic Stratification Based on Differential Expression Invasion Genes of Molecular Subtypes

Abstract: Background. The acquisition of invasive tumor cell behavior is considered to be the cornerstone of the metastasis cascade. Thus, genetic markers associated with invasiveness can be stratified according to patient prognosis. In this study, we aimed to identify an invasive genetic trait and study its biological relevance in lung adenocarcinoma. Methods. 250 TCGA patients with lung adenocarcinoma were used as the training set, and the remaining 250 TCGA patients, 500 ALL TCGA patients, 226 patients with GSE31210,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 41 publications
(21 reference statements)
1
3
0
Order By: Relevance
“…The four types of ISs presented different molecular characteristics, which were reflected in the differences in the number of TMB, mutant genes, chemokines and chemokine receptors. We observed that TP53 mutations were the most common, which was consistent with previous studies ( 38 ). A growing body of findings supported the correlation of differential existence of components of the immune system in deciding the evolution of cancer ( 39 ).…”
Section: Discussionsupporting
confidence: 93%
“…The four types of ISs presented different molecular characteristics, which were reflected in the differences in the number of TMB, mutant genes, chemokines and chemokine receptors. We observed that TP53 mutations were the most common, which was consistent with previous studies ( 38 ). A growing body of findings supported the correlation of differential existence of components of the immune system in deciding the evolution of cancer ( 39 ).…”
Section: Discussionsupporting
confidence: 93%
“…To further assess the relationship between the risk score and immune prognosis, we examined the PD-L1 expression levels between the two risk subgroups and found that PD-L1 expression levels were significantly higher in the high-risk group than in the low-risk group, consistent with the fact that Luo et al also showed significant differences in PD-L1 expression between the low- and high-risk groups in patients with LUAD ( Luo et al, 2020 ). In addition, we compared the mutation characteristics of the high-risk and low-risk groups and found that TP53 mutations were more common in the high-risk population, which was also identified in one study that found a higher frequency of TP53 mutations in the C1 subtype of LUAD ( Zheng et al, 2020 ). Finally, we validated the expression of prognostic lncRNAs in clinical LUAD tissues and found expression trends consistent with two public databases, with one study showing that LINC00857 expression was significantly upregulated in LUAD paraneoplastic tissues compared to normal lung tissue ( Wang et al, 2020 ), which is consistent with our results.…”
Section: Discussionmentioning
confidence: 63%
“…8 Zheng et al developed prognostic risk models based on differentially expressed IRGs in different molecular subtypes of LUAD. 9 Therefore, studying invasion-related markers to ensure earlier treatment can potentially improve the prognosis and survival of cancer patients.…”
Section: Introductionmentioning
confidence: 99%